PENGARUH SOSIAL MEDIA INFLUENCER DAN PROMOSI PENJUALAN TERHADAP MINAT BELI PADA BISNIS KULINER UMKM DI PALEMBANG INDAH MALL - Damara, Rentika; Widiyanti, Marlina; Shihab, Muchsin Saggaf; Rosa, Aslamia (Jurnal Ilmiah Global Education, 2023)
This research was conducted with the aim of testing empirically by analyzing the influence of social media influencers and sales promotions on buying interest in the culinary business at Palembang Indah Mall. The population in this study are Micro, Small and Medium Enterprises (MSMEs) interested in the food and beverage culinary business in Palembang Indah Mall with a sample of 100 people who will be distributed to MSME enthusiasts in Palembang Indah Mall using the random method. sampling. The results obtained are influencer social media and sales promotion which have a significant positive effect on buying interest in culinary MSME businesses in Palembang Indah Mall. Suggestions that can be given for further research are for MSMEs to be more selective in choosing the role of influencers who can be trusted, have culinary knowledge, be honest with the messages conveyed, and be able to display culinary qualities that are easy to understand when carried out online or directly promoted on social media. Future researchers are expected to add other variables such as celebrity endorsement, word of mouth, online advertising, brand image, discount framing, and so on..